The Routledge handbook of hospitality management - Pantelidis, Ioannis S. (Current developments in the geographies of leisure and tourism, 2014)
Hospitality is an industry characterized by its complex nature and numerous sectors including hotels, hostels, B&Bs, restaurants, pubs, nightclubs and contract catering. However, despite its segmentation, there are key issues that are pertinent to all subsectors. The Routledge Handbook of Hospitality Management adopts a strategic approach and explores and critically evaluates current debates, issues and controversies to enable the reader to learn from the industry s past mistakes as well as future opportunities. Especially relevant at a time when many sectors of the industry have to re evaluate and reinvent themselves in response to the economic downturn the Handbook brings together specialists from both industry and academia and from a range of geographical regions to provide state of the art theoretical reflection and empirical research. Each of the five inter related sections explores and evaluates issues that are of extreme importance to hospitality organizations, many of which have not been adequately explored before: external and internal customers, debates surrounding finance, uncertainty risk and conflict, sustainability, and e-Hospitality and Technology. This book is an invaluable resource for all those with an interest in hospitality, encouraging dialogue across disciplinary boundaries and areas of study. It is essential reading for students, researchers & academics and managers of Hospitality as well as those of Tourism, Events, Marketing, and Business Management.